Quantitative identification of ventral/dorsal nerves through intraoperative neurophysiological monitoring by supervised machine learning - Jiang, Wenbin; Zhan, Qijia; Wang, Junlu; Wei, Min; Li, Sen; Mei, Rong; Xiao, Bo (Frontiers in Pediatrics, 2023)
Objective This study aimed to investigate the electro-neurophysiological characteristics of the ventral and dorsal nerves at the L2 segment in a quantitative manner. Methods Medical records of consecutive patients who underwent single-level approach selective dorsal rhizotomy (SDR) from June 2019 to January 2022 were retrospectively reviewed. Intraoperative electro-neurophysiological data were analyzed. Results A total of 74 males and 27 females were included in the current study with a mean age of 6.2 years old. Quadriceps and adductors were two main muscle groups innervated by L2 nerve roots in both ventral and dorsal nerve roots. Dorsal roots have a higher threshold than that of the ventral ones, and muscles that first reached 200 µV innervated by dorsal roots have longer latency and smaller compound muscle action potential (CMAP) than those of the ventral ones. Supervised machine learning can efficiently distinguish ventral/dorsal roots using threshold + latency or threshold + CMAP as predictors. Conclusion Electro-neurophysiological parameters could be used to efficiently differentiate ventral/dorsal fibers during SDR.